2009
DOI: 10.1002/art.24336
|View full text |Cite
|
Sign up to set email alerts
|

Does knee malalignment increase the risk of development and progression of knee osteoarthritis? A systematic review

Abstract: Objective. To systematically review the evidence for a relationship between malalignment of the knee joint and progression and/or development of knee osteoarthritis (OA). Methods. Electronic searches of Medline, EMBase, and CINAHL were performed up to July 2008 using medical subject headings and free-text words. We included radiographic or magnetic resonance imaging (MRI) studies that met a set of predefined criteria. Two independent reviewers extracted the data and assessed the methodologic quality of the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
230
2
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(249 citation statements)
references
References 29 publications
6
230
2
11
Order By: Relevance
“…In the present study, only valgus alignment (and not varus alignment) was significantly associated with an unfavorable outcome at 6-year followup. This is in contrast to a recent systematic review that found an independent relationship between both valgus and varus alignment and OA of the knee (29). However, they used radiographic and magnetic resonance imaging methods that may have contributed to the difference of our results.…”
Section: Discussioncontrasting
confidence: 98%
“…In the present study, only valgus alignment (and not varus alignment) was significantly associated with an unfavorable outcome at 6-year followup. This is in contrast to a recent systematic review that found an independent relationship between both valgus and varus alignment and OA of the knee (29). However, they used radiographic and magnetic resonance imaging methods that may have contributed to the difference of our results.…”
Section: Discussioncontrasting
confidence: 98%
“…The study was only conducted in patients with medial compartment OA; therefore, it is not possible to generalize to patients with lateral compartment OA or patellofemoral disease. There was no assessment of varus-valgus alignment in this study, which has been recognized as a risk factor for radiographic progression (23,24). Recent studies using MRI have indicated that meniscal pathology is common in patients with knee OA, and degeneration and extrusion of the meniscus may also be reflected in loss of JSW using plain radiography (25).…”
Section: (3)mentioning
confidence: 84%
“…Previous systematic reviews have sought to identify predictors of knee OA progression using radiographic change (5,6) or functional decline and change in pain (7) as outcome measures. Usual clinical practice is to gather information from both radiographs and patient-reported symptoms.…”
Section: Introductionmentioning
confidence: 99%